Tax Avoidance In Healthcare Sector Companies: An Analysis Of Sales Growth, Capital Intensity, and The Moderating Role Of Institutional Ownership - Putri, Anggitha Wiguna; Syahrudin, Muhammad; Sari, Laras Angelia Nirwana (Journal of Accounting Inaba, 2025)
This study aims to analyze the effect of sales growth and capital intensity on tax avoidance, with institutional ownership as a moderating variable, in healthcare sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. The research employs a quantitative approach with a descriptive-associative design. Secondary data were obtained from company financial statements, with a total of 39 observations selected using purposive sampling. The analysis was conducted using panel data regression and Moderated Regression Analysis (MRA) with EViews 13 software. The findings reveal that sales growth and capital intensity have no significant effect on tax avoidance. Furthermore, institutional ownership does not moderate the relationship between sales growth or capital intensity and tax avoidance. This study offers insights for regulators to improve fiscal oversight in the healthcare sector.  This study contributes to the literature on tax governance and provides practical implications for regulators to strengthen fiscal oversight policies.